Jouer un scénario d’aménagement foncier : analyse des pratiques d’aménagement et recherche d’alternatives au développement résidentiel - Laure Casanova Enault; Marta Debolini; Tatiana Popoff; Roxane De Flore (Netcom)
Mediterranean coastal territories are concerned by land and real estate markets pressures and by environmental pressures related to the touristic and residential development models. This context implies land-related conflicts. In this paper, we proposed a planning game, ALTERé, applied to two intermunicipalities of the coastal Var’s Department in order to meet two main objectives : firstly, to develop an oriented formation to train different actors of spatial planning in terms of sustainable development stakes and secondly, to analyze how an alternative scenario of planning is set up. Composed by four sequences, the game enables a space of concertation between actors with some arguing interests. The achieved results concerned identifications of strategic areas, disagreements on the territorial project and indications for public action. This approach could be generalized to other territories and to other planning scenarios.